Carbon emission quantification analysis of excavation engineering under road transport conditions. - Bai Chongxi; Zhiheng Zhang (PLoS ONE)
Current research on building carbon emissions primarily focuses on various carbon emission assessment models and the use of life cycle analysis to evaluate overall building carbon emissions, with limited attention given to excavation engineering. Based on the life cycle method and process analysis, this study analyzes carbon emissions in excavation engineering by optimizing the evaluation model for fuel consumption standards of freight vehicles during the transportation phase in China. To account for the difference between actual and rated fuel consumption of transport vehicles, factors such as road conditions, traffic congestion, and temperature are introduced to adjust the carbon emission calculation model for the transportation phase. This approach reasonably incorporates the impact of fuel consumption during vehicle idling on carbon emission calculations. Using the 02B excavation of the Beijing Sub-Center Station transportation hub as a case study to validate the proposed method, the analysis reveals that the primary source of carbon emissions in excavation engineering is earthwork transportation, accounting for 40.50% of total emissions. Among these, earthwork transportation contributes 95.28% of emissions within the transportation phase. Due to adjustments in the carbon emission calculation model for the transportation phase, carbon emissions increased by 1,226.79 tons, accounting for 9.2% of the total. The revised model provides a theoretical basis for accurately assessing carbon emissions in excavation engineering.